2010
DOI: 10.1007/978-3-642-12384-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Self-adaptive Coordination for Robot Teams Accomplishing Critical Activities

Abstract: This paper presents a Self-Adaptive cooperation model for autonomous mobile devices, to achieve collaborative goals in crisis management scenarios. The model, which is based on the AMAS theory, allows dynamic team formation, task allocation and reconfiguration. The global behaviour emerges from interactions among individual agents. Task responsibility allocation is done by individual estimations of the degree of difficulty and priority to achieve the task. Then each peer exchanges its evaluation records with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Indeed, some initial experiments have started implementing the AMAS cooperation model so far where robots are considered AMAS agents with same capabilities (e.g. [17,18,21]). Team members have neither information nor explicit representation of the team's objectives.…”
Section: Developing Team Cooperation Models In the Experimental Framementioning
confidence: 99%
“…Indeed, some initial experiments have started implementing the AMAS cooperation model so far where robots are considered AMAS agents with same capabilities (e.g. [17,18,21]). Team members have neither information nor explicit representation of the team's objectives.…”
Section: Developing Team Cooperation Models In the Experimental Framementioning
confidence: 99%
“…In the scenario, the objective of the AMAS AGVs is to plan and allocate tasks (to move to a destination to "rescue" a victim) among them. For that, each AMAS AGV follows a perceive-decide-act lifecycle and exchange messages with other AMAS AGVs by following a cooperative task allocation protocol defined using the AMAS theory (see [5]). Tweaks of the behaviour are focused on the evaluation of tasks criticality and their acceptation.…”
Section: Identification Of the Speciesmentioning
confidence: 99%
“…They can be applied to a wide range of applications thanks to their intrinsic properties and features such as simplicity, flexibility, reliability, self-organization/emergent phenomena, low cost agent design and adaptation capacity. It has been shown that reactive multi-agent system are efficient to tackle complex problems [14], cooperation of situated agents/robots [15], data fusion and problem/game-solving [13]. In this context, our proposal consists in decision making by evaluating emergent properties of agent's organization.…”
Section: Introductionmentioning
confidence: 99%